2014
DOI: 10.1002/aqc.2483
|View full text |Cite
|
Sign up to set email alerts
|

Pacific oysters, Crassostrea gigas, established in Scotland

Abstract: A report to Scottish Natural Heritage on European flat oysters, Ostrea edulis, surviving in the Firth of Forth was investigated. No live O. edulis were found, but eight feral Pacific oysters, Crassostrea gigas, were found attached to eulittoral boulders and bedrock. The ages of the Pacific oysters indicated an initial settlement no later than 2007 and at least two subsequent settlements, which may have been from recruitment in situ, or from repeated introductions of larvae. The mode of introduction is unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Widely introduced into Northern European waters in the mid-1960s to support the aquaculture industry at risk as a result of declining native oyster populations, spawning 3 and external recruitment 34 was thought to be inhibited by low water temperatures in the northmost regions. Persistence of wild oyster reefs is now heavily reported in North West Europe 10 , 12 , including on the South coast of England and Wales, and occasional isolated settlements in cooler Scottish waters 28 , 29 , which has been linked to recent warm summers that facilitate spawning 11 , 28 , 30 – 33 and to external larval recruitment from local aquaculture sites and more distant populations, shipping, and live trade 34 . However, persistence of wild oysters can be unpredictable even under favorable temperature conditions 11 , 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Widely introduced into Northern European waters in the mid-1960s to support the aquaculture industry at risk as a result of declining native oyster populations, spawning 3 and external recruitment 34 was thought to be inhibited by low water temperatures in the northmost regions. Persistence of wild oyster reefs is now heavily reported in North West Europe 10 , 12 , including on the South coast of England and Wales, and occasional isolated settlements in cooler Scottish waters 28 , 29 , which has been linked to recent warm summers that facilitate spawning 11 , 28 , 30 – 33 and to external larval recruitment from local aquaculture sites and more distant populations, shipping, and live trade 34 . However, persistence of wild oysters can be unpredictable even under favorable temperature conditions 11 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic settlements of Pacific oysters were detected in the early-1990s in the UK 27 . Likely the consequence of global climate change, persistent wild M. gigas populations are now reported throughout the UK coastline, with substantial settlements in the South of England and Wales, and more isolated individual settlement occasionally seen in more northern and cooler waters 28 , 29 . In particular, warmer summer temperature has increased the frequency of spawning events and facilitated development and maturation of M. gigas , therefore aiding settlement and persistence of populations in the UK 11 , 28 , 30 – 33 , and other parts of the North West Europe 10 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Wild establishment as a direct result of introductions into marinas, harbours and ports from boat traffic as fouling or entrained larvae are as yet unproven but suspected. In the UK there are coastal regions where wild settlement is occurring that is distant from Pacific oyster production (Herbert et al 2012;Smith et al 2015). Moreover in Lough Foyle on the north coast of Ireland, wild oysters were shown to be genetically different from current stock obtained from local oyster farms (Kochman et al 2012).…”
Section: Policy Framework and Management Measuresmentioning
confidence: 99%
“…As in the Oosterschelde it may be possible to provide financial incentives to support and develop a sustainable industry, particularly where dense reefs have not yet formed, as individual oysters have far greater value than those with distorted shells. For example in ports, harbours and marinas, where fouled vessel traffic is suspected of contributing to wild settlement (Herbert et al 2012;Smith et al 2015), harvesting oysters may be a viable way of controlling the stock. Business start-up schemes and fisheries and aquaculture support schemes could be appropriate avenues for support ( Fig.…”
Section: Opportunities Through Hand-collecting and Fishingmentioning
confidence: 99%
“…In places, this species has become naturalised (Ruesink et al 2005); for example, C. gigas natural spatfall was recorded in the Oosterschelde estuary (southwest N etherlands) in 1975 (Smaal et al 2009), and their presence was reported in the East Frisian Wadden Sea, North Sea, between 2003and 2005(Brandt et al 2008. C. gigas has been reported in Strangford Lough in N orthern Ireland from the 1990s (Guy & Roberts 2010), as well as Scotland (Smith et al 2015) and as far north as Sweden and Norway (Wrange et al 2010). Information from experimental studies on C. gigas (e.g.…”
Section: Introductionmentioning
confidence: 99%